Longitudinal relationships between maturation, technical efficiency, and performance in age-group swimmers: improving swimmer evaluation - Abbott, S.; Yamauchi, G.; Halaki, M.; Castiglioni, M. T.; Salter, J.; Cobley, S. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The study aimed to (1) accurately examine longitudinal relationships between maturity status and both technical skill indices and performance in Australian male (N = 64) age-group Front-crawl swimmers (10-15 y) and (2) determine whether individual differences in maturation influenced relationships between technical skill level and swimming performance.